ЧИСЛЕННО-ПОЛЕВОЙ АНАЛИЗ ВРЕМЕННЫХ ФУНКЦИЙ И ГАРМОНИЧЕСКОГО СОСТАВА ЭДС В ОБМОТКАХ ТРЕХФАЗНОГО АСИНХРОННОГО ДВИГАТЕЛЯ - Милых, В.И. (Інститут електродинаміки НАН України, Київ, 2018)
The principles and results of the numerical-field determination and harmonic analysis of EMF in windings of three-phase asynchronous motors with a short-circuited winding of the rotor have presented. This has realized in dynamics by multi-position calculations of the rotating magnetic field with the finite element method by the FEMM software environment. Calculations have automated by the control program in the algorithmic language Lua. The analysis has carried out for the phase winding of the stator and various rods of the rotor winding under load conditions and artificial idle modes. The basic functions to determine the temporal functions of the EMF are analogous functions of magnetic flux linking obtained in discrete numerical form. The transition to EMF has carried out through the expansion of certain functions into harmonic series and also in finite-difference form. To test the presented method of EMF a 15 kW motor has used analysis. The complex nature of the temporal functions of EMF and their wide harmonic spectra have revealed. References 17, tables 2, figures 11.